Determination of critical breakage conditions for double glazing in fire. (25th January 2017) - Wang, Yu; Li, Ke; Su, Yanfei; Lu, Wei; Wang, Qingsong; Sun, Jinhua; He, Linghui; Liew, K.M.
Highlights: Critical heat fluxes of exposed and ambient panes are 6 kW/m 2 and 25 kW/m 2 . Critical temperature difference of fire side pane is around 60 °C. The ambient pane survives three times longer due to radiation filter and air gap. Heat transfer in double glazing is revealed by a heat flux based theoretical model. Abstract: Double glazing unit normally demonstrates better fire resistance than single glazing, but the knowledge on its thermal behavior and heat transfer mechanism during fire is limited. In this work, nine double glazing units were heated by a 500 × 500 mm 2 pool fire. The incident heat flux, temperature on four surfaces, breakage time and cracking behavior were obtained. The critical breakage conditions for interior and exterior panes were determined through gradually decreasing the glass-burner distance from 750 mm to 450 mm. It is established that in double glazing the pane at ambient side can withstand significantly more time than the pane exposed to fire. The critical temperature difference for interior pane is 60 °C; the critical temperature of exterior pane breakage is much higher due to no frame-covered area. In addition, the heat flux at the time of crack initiation is 6 kW/m 2 for the pane at fire side, while more than 25 kW/m 2 for ambient side pane. To reveal the heat transfer mechanism in glazing-air-glazing, theoretical and numerical investigations are also performed, which agrees well with the experimental results.